Hubungan Antara Penerapan Phbs Tatanan Rumah Tangga Dengan Kejadian Diare Pada Balita Di Wilayah Kerja Puskesmas Jatilawang - Saputra, Bayu Aji; Hikmawati, Isna (Jurnal Keperawatan Muhammadiyah, 2020)
Background: According to data compiled from the Ministry of Health of the Republic of Indonesia in 2017, Central Java ranks third with the highest diarrhea cases in all of Indonesia with 911,901 patients. Moreover, based on the data from the Banyumas Health Profile (2018), diarrhea cases reached 36,696 cases and the sub-district with the most diarrhea cases was Jatilawang sub-district with 1,483 cases. Objective: To determine the correlation between the application of PHBS (Perilaku Hidup Bersih dan Sehat), a term used to describe clean and healthy living behaviour, in the household o and the occurrence of diarrhea in toddlers in the service area of Jatilawang Community Health Care Center. Method: the method used in this study was descriptive-analytic with case-control approach. Purposive sampling technique was applied in this study in which there were as many as 26 respondents that complemented with the inclusion and exclusion criteria applied. The research instrument used in this study were questionnaire sheets and observational sheets. The data collected in this study were then analyzed using the Chi-Square test. Results: This result of the study showed that there was a relationship between clean and healthy living behavior (PHBS) of the household order and the occurrence of diarrhea in toddlers in the Jatilawang Public Health Center working area with a value of 0.005 (p value 0.05) and an odd ratio value (OR) = 12.375 with CI value = 1,828-83,767 Conclusion: There is a correlation between clean and healthy living behavior (PHBS) of the household order and the occurrence of diarrhea in toddlers in the service area of Jatilawang Public Health Center.Keywords: Application of PHBS household order, the incidence of diarrhea, toddlers